2022
DOI: 10.1002/cssc.202200449
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Reversible pH Control Process for the Formation and Dissociation of Lignin Nanoparticles

Abstract: As a new and green type of nanomaterials, lignin nanoparticles (LNPs) have been considered as high-value renewable materials for application in many fields. However, the industrialization of LNPs faces many challenges, such as high manufacturing costs and small-scale production. Here, a simple but rapid and reversible approach for the fabrication of LNPs was provided via switching pH environments. The LNPs were regularly shaped in the acetonitrile/water system, and their size appeared to be very homogeneous. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In this study, the micromorphology of the lignin fractions was investigated by scanning electron microscope (SEM), and the SEM images of sub-micron lignin spheres are presented in Figure 3 . It can be observed that BLs presented some regular micro-nanoparticles with different sizes, suggesting that lignin was well self-assembled during the recovery process from black liquor ( Xu et al, 2022 ). Then, the recovered DES lignin also exhibited a micro-nanoparticle shape, in which the L EG and L Gly showed a relatively regular and large micro-nanoparticle shape.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the micromorphology of the lignin fractions was investigated by scanning electron microscope (SEM), and the SEM images of sub-micron lignin spheres are presented in Figure 3 . It can be observed that BLs presented some regular micro-nanoparticles with different sizes, suggesting that lignin was well self-assembled during the recovery process from black liquor ( Xu et al, 2022 ). Then, the recovered DES lignin also exhibited a micro-nanoparticle shape, in which the L EG and L Gly showed a relatively regular and large micro-nanoparticle shape.…”
Section: Resultsmentioning
confidence: 99%
“…Lignin is a natural polyphenolic antioxidant and a broad-spectrum sunscreen . Lignin contains a large number of chromophore structures such as benzene rings, carbonyl groups, and phenolic hydroxyl groups and has a high absorbance at 280–300 nm, which provides an excellent UV protection .…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is a natural polyphenolic antioxidant and a broadspectrum sunscreen. 6 Lignin contains a large number of chromophore structures such as benzene rings, carbonyl groups, and phenolic hydroxyl groups and has a high absorbance at 280−300 nm, which provides an excellent UV protection. 7 The development of lignin nanoparticles in the past decade has not only cleverly avoided the nonhomogeneity of lignin but also endowed it with a variety of nanomaterial properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared to colloidally unstable and interpenetrating micro- and larger-sized lignin particles, the lignin nanoparticles (LNPs) display enhanced adsorption ability at the oil–water interface of the emulsions, which are beneficial to the formation of stable and homogeneous Pickering emulsions [ 24 ]. Up to now, various methods have been explored to prepare LNPs, e.g., acidic precipitation [ 25 ], solvent exchange [ 26 ], solvent–antisolvent [ 27 ], ultrasonication polymerization [ 28 ], biological treatment [ 29 ], etc. The solvent–antisolvent technology is the most commonly used method due to its easy implementation process and the generated LNPs with controllable sizes.…”
Section: Introductionmentioning
confidence: 99%